1996
DOI: 10.1007/bf02065942
|View full text |Cite
|
Sign up to set email alerts
|

Transport intracytoplasmic sperm injection (ICSI): A cost-effective alternative

Abstract: These results suggest that long-distance transport of human oocytes seems not to be harmful to their capacity to be successfully injected and to further embryonic development and their implantation potential. Transport ICSI seems to be a valuable and cost-effective approach to treat high numbers of patients at a restricted number of highly specialized IVF laboratories, especially in countries where ICSI is not commonly available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…PREVIOUS TRANSPORT ART studies have already indicated no differences in rates of fertilization, cleavage, transfer or pregnancy with conventional IVF and ICSI using the transport oocyte method and performed entirely at the ART center. Delay as a result of transportation in commencement of culture does not reduce the pregnancy rate, reduce the ability during ICSI of the oocyte to endure sperm injection, or subsequent embryo development and ability to implant 7–16 . We have also achieved favorable results with our round trip method, where transported fresh embryos are implanted at satellite clinics 6,17,18 .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…PREVIOUS TRANSPORT ART studies have already indicated no differences in rates of fertilization, cleavage, transfer or pregnancy with conventional IVF and ICSI using the transport oocyte method and performed entirely at the ART center. Delay as a result of transportation in commencement of culture does not reduce the pregnancy rate, reduce the ability during ICSI of the oocyte to endure sperm injection, or subsequent embryo development and ability to implant 7–16 . We have also achieved favorable results with our round trip method, where transported fresh embryos are implanted at satellite clinics 6,17,18 .…”
Section: Discussionmentioning
confidence: 88%
“…Delay as a result of transportation in commencement of culture does not reduce the pregnancy rate, reduce the ability during ICSI of the oocyte to endure sperm injection, or subsequent embryo development and ability to implant. [7][8][9][10][11][12][13][14][15][16] We have also achieved favorable results with our round trip method, where transported fresh embryos are implanted at satellite clinics. 6,17,18 These results suggest that transport does not affect the viability of oocytes or fresh embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Transport IVF is used in other countries in Europe ( Kingsland et al ., 1992 ; De Sutter et al ., 1996 ; Qureshi et al ., 1997 ), Canada ( Buckett et al ., 1999 ) and Japan ( Takanashi et al ., 2004 ). Fresh embryo transport is also available in the USA ( Langley et al ., 2001 ), Ukraine ( Levron et al , 2014 ), and Japan ( Takanashi et al, 2005 ), with satisfying results.…”
Section: Discussionmentioning
confidence: 99%
“…P REVIOUS REPORTS OF transport assisted reproductive technology (ART) suggest that transportation per se does not adversely affect the oocytes. [1][2][3][4][5][6][7][8] During the past 6 years, we have used transport ART in more than 250 patients, collecting oocytes from more than 350 cycles. Our transport ART network comprises the center facility (at the Department of Obstetrics and Gynecology, Omori Hospital attached to the Toho University School of Medicine, Tokyo, Japan) and satellites, including three facilities that use the round-trip method in which oocytes and embryos are transported between the main ART center and the satellite facilities, 9,10 11 facilities that use the one-way method for oocytes, one facility that transports embryos to the center for cryopreservation, 11 and three facilities where the ART treatment modality is selected on an individual basis ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…PREVIOUS REPORTS OF transport assisted reproductive technology (ART) suggest that transportation per se does not adversely affect the oocytes 1–8 . During the past 6 years, we have used transport ART in more than 250 patients, collecting oocytes from more than 350 cycles.…”
Section: Introductionmentioning
confidence: 99%